Acute retinal toxicity associated with a mixture of perfluorooctane and perfluorohexyloctane: failure of another indirect cytotoxicity analysis. Issue 1 (29th March 2018) - Coco, Rosa M; Srivastava, Girish K; Andrés-Iglesias, Cristina; Medina, Jesús; Rull, Fernando; Fernandez-Vega-Gonzalez, Alvaro; Fernandez-Bueno, Ivan; Dueñas, Antonio; Pastor, Jose C
Abstract : Aims: To report new information related to acute retinal toxicity of Bio Octane Plus, a mixture of 90% perfluorooctane (PFO) and 10% perfluorohexyloctane. Methods: This retrospective, descriptive case series reports the occurrence of acute retinal toxicity after vitreoretinal surgery in which Bio Octane Plus (batch number 1605148) was used as an endotamponade. Cytotoxicity biocompatibility tests and chemical analyses by Fourier-transformed infrared (FTIR) spectroscopy and gas chromatography-mass spectrometry (GC-MS) of the presumed toxic product were performed. Results: Four patients presented with acute severe visual loss after uneventful ocular surgery assisted by Bio Octane Plus (batch number 1605148) as endotamponade. Patients experienced extensive retinal vascular occlusion leading to retinal and optic nerve atrophy. The viability of ARPE-19 cells directly exposed to the suspect batch for 30 min was 0%. The agarose overlay method used by the manufacturer according to European Union regulations and International Organization for Standardization (ISO) International Standards failed to detect toxicity. FTIR spectroscopy showed small differences between the non-toxic and toxic batches. GC-MS analysis showed the presence of bromotributyl stannane (whose toxicity was demonstrated in the dose–response curve) only in the toxic batch of Bio Octane Plus. Conclusion: This is the third report of retinotoxicity due to PFO in 4 years. The clinical profiles may be missed as they resemble other postsurgical complications; therefore, more cases worldwide could have gone unreported. Protocols to determine cytotoxicity of intraocular medical devices and approved by the ISO International Standards based on indirect methods have failed and should be revised to ensure safety.